Multi-tissue transcriptomic analysis reveals that L-methionine supplementation maintains the physiological homeostasis of broiler chickens than D-methionine under acute heat stress. - Mingyung Lee; Hyesun Park; Jung Min Heo; Ho Jun Choi; Seongwon Seo (PLoS ONE)
The objective of this study was to compare the effects of supplementation with two methionine isoforms, L-methionine (L-Met) or D-methionine (D-Met), on transcriptome expression in broiler chickens under acute heat stress. A total of 240 one-day-old chicks were randomly assigned to one of four treatments in a 2 × 2 factorial arrangement: thermo-neutral vs. acute heat-stress and L-Met vs. D-Met supplementation. On day 14, the heat-stressed group was exposed to 32°C for 5 h, while the others remained at 25°C. Six chicks were randomly selected per treatment and total RNA was isolated from whole blood, ileum, and liver tissues. Two RNA samples from each tissue of each treatment group were randomly selected and pooled in equal amounts. A total of 1.87 billion raw reads obtained from 36 samples (four treatments × three tissues × three composited replicates) were mapped to the reference genome build (Gallus_gallus-5.0) and used to identify differentially expressed genes (DEGs) using DESeq2. Functional enrichment of DEGs was tested using DAVID. Comparing the two isoforms of supplemented methionine, two, three, and ten genes were differentially expressed (> 1 or < -1 log2 fold change) in whole blood, ileum, and liver, respectively. A total of 38, 71, and 16 genes were differentially expressed in response to the interaction between heat stress and Met isoforms in the blood, ileum, and liver, respectively. Three-tissue-specific DEGs were functionally enriched for regulation of cholesterol homeostasis and metabolism, glucose metabolism, and vascular patterning. Chicks fed with L-Met had lower immune (e.g., IL4I1 and SERPINI1) and intestinal angiogenic responses (e.g., FLT1 and FGD5), and stable glucose and lipid metabolism (e.g., PCK1 and LDLR) under heat stress conditions. In conclusion, unlike D-Met, L-Met supplementation seems to help maintain physiological homeostasis and enhances cellular defense systems against external stresses like high environmental temperature.